Outcome of tap block in the cesarean section on postoperative pain - Dr. Noor Alimardan Mohamad; Dr. Layth Masood Saleh; Dr. Ayad Najm Abdulameer (Genius Journals, 2022)
(TAP) is a new method for bilateral blockade of afferent abdominal wall nerves through small lumbar triangles. Aim We evaluated its analgesic efficacy in patients within the first 24 hours of pregnant women who underwent caesarean section in a randomized, double-blind clinical trial METHODS: 90 pregnant women who underwent cesarean delivery, including patient-controlled analgesics with morphine, were selected; in this paper, the focus was on the extent of the degree of pain to patients who underwent TAP in caesarean section, where information and demographic data were collected from different hospitals in Iraq. Patients were distributed into two groups: 45 patients who underwent TAP and 45 patients' group. The control ages ranged from 20-40 years. RESULTS: TAP block reduced visual analogue pain scores (TAP vs. control, mean ± S.D. p < 0.05), and at all postoperative time points, including 24 h after surgery. Morphine requirement was also reduced in the first 24 h after surgery, where the mean SD to morphine for the group of patients was 6.78 ± 2.56, while for the control group, it was significantly less than 4.99 ± 1.1. The prevalence of complications or negative aspects in this study to patients in the TAP group was eight patients, while in the control group, it was for 19 patients and all patients who received TAP reported a high level of satisfaction with the analgesic regimen after surgery
Keywords: TAP; BMI; VAS; Patients